Ice force - Lynn, Matthew (London : Headline, 2012)
A plane carrying a Russian oil billionaire has crashed mysteriously in the Arctic in the middle of a brutal winter. Nobody knows why, nor can they locate the aircraft's black box.
Keywords: Arctic regions -- Fiction; Thrillers (Fiction)